Counseling on Clean and Healthy Living Behavior in Improving Public Health Levels - Astutik, Wiwin Dwi; Sadiyah, Vaneza Kalema; Siswanto, Deny Hadi (The Indonesian Institute of Science and Technology Research, 2025)
This activity aims to enhance public awareness and participation in implementing Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat or PHBS) through interactive counseling methods, education in elementary schools, and community service initiatives. Counseling is conducted through question-and-answer sessions to ensure participants' understanding, while education in elementary schools teaches proper handwashing practices as a preventive measure. Additionally, community service involves the public in maintaining environmental cleanliness. The evaluation results indicate improved public understanding of PHBS based on pretest and posttest scores. The average score of housewives increased by 11.61%, while elementary school students showed an improvement of 19.71%. This increase demonstrates that interaction-based counseling methods are more effective than one-way lectures in enhancing comprehension and behavioral change. With growing public awareness of PHBS, it is expected that healthy behaviors can be consistently practiced in daily life, contributing to a cleaner and healthier environment. This study recommends an interactive approach and hands-on practice in health education programs to enhance the effectiveness of long-term behavioral change.